In-situ observation of the initiation of plasticity by nucleation of prismatic dislocation loops - Subin Lee (Nature Portfolio, 2020)
Prismatic dislocation loops (PDLs) form during the elastic-to-plastic transition of a dislocation-free volume under nanoindentation. Here the authors observe the initial plasticity and burst-like emission of PDLs in Au nanowires by in-situ transmission electron microscopy, elucidating fundamental aspects of the formation process.